Training of parental scaffolding in high-socio-economic status families: How do parents of full- and preterm-born toddlers benefit? - Erdmann, Kim; Vetter, Verena; Schäferling, Michaela; Reuner, Gitta; Hertel, Silke (British journal of educational psychology, 2018)
Background Preterm children have an increased risk regarding self-regulation development. Given the strong link between parenting behaviour (i.e., scaffolding and sensitivity) and children's self-regulation, parental training presents a promising way to counteract the negative consequences of preterm birth. Aims We explored the effectiveness of parental training by comparing a basic scaffolding training and a combined scaffolding/sensitivity training to an active treatment-control group (stress management). Basic and combined treatments should increase parents’ domain-specific self-efficacy (DSSE) and beliefs on parental co-regulation and the promotion of learning (BCL) more than the control treatment should. No such differences were expected for parents’ domain-general self-efficacy (DGSE). We examined whether parents of preterm and full-term children benefitted equally from training conditions. Sample(s) A total of 87 parents of full-term and 35 parents of preterm toddlers (24-36 months of age, corrected for prematurity) participated. Methods Based on a quasi-experimental pre-test-post-test follow-up design, parents were randomly assigned to treatments. A multimethod approach was applied, including self-report, parent-child interactions, and standardized behavioural tasks. The presented study is limited to questionnaire data on parents’ DGSE, DSSE, and BCL. Results An overall increase resulted from pre- to post-test and/or follow-up. Parents’ BCL changed significantly stronger in the combined training than in the control group. Parents of preterm and full-term children benefitted equally from basic and combined training. Conclusions The combined training enhanced BCL among parents of full-term and preterm children the most. If such training also yields improvement on the behavioural level, this finding will advance preterm aftercare.